USING COOPERATIVE LEARNING IN A GRAMMAR WORKSHOP: A CASE STUDY ON STUDENTS´ PERCEPTIONS - Machado, Isabel; Coimbra, Nazaré (Advances in Social Sciences Research Journal, 2015)
This work intends to study the effectiveness of the application of cooperative learning techniques in grammar, in the context of a Grammar Workshop, in Portuguese as mother tongue. It was used a qualitative approach, a case study, focused on group work, comprising students of the 9th grade, in a public Portuguese school. The results show that students have different perceptions regarding the teaching and learning of grammar, although they all recognize its importance for the development of language and communication skills. The students point out some advantages of the method of cooperative learning, such as the easiness of learning grammar and the improvement of their academic results on Portuguese language. They also refer a more positive attitude towards learning grammar, together with the development of linguistic and social skills.